HOW MUCH ARTISTIC GYMNASTICS COACHES KNOW ABOUT THEIR GYMNASTS’ MOTIVATION - Myrian Nunomura; Yoshinori Okade; Paulo Carrara (Science of Gymnastics Journal)
Sport seems to increasingly attract children and youth participation worldwide, possibly because many of them dream of competing in the Olympics, becoming champions, and being financially rewarded. However, only a few are aware of the level of commitment and sacrifices required in order to succeed. The purpose of this study was to analyze the Brazilian coaches’ perceptions of their athletes’ motivation and how they deal with this issue. Results revealed that Artistic Gymnastics training seems to highly demand gymnasts’ motivation to practice, and some strategies used by coaches to motivate gymnasts should be carefully reviewed. Other motivational strategies are limited due to the circumstances of the sport in Brazil, particularly regarding investment in infrastructure and support for gymnasts.